Myoadenylate deaminase deficiency does not affect muscle anaplerosis during exhaustive exercise in humans - Tarnopolsky, Mark A (Blackwell Science Inc, 2001)
1. Myoadenylate deaminase (AMPD) deficiency is present in 1–2 % of the population. In theory, this deficiency may alter exercise energy metabolism by impairing the purine nucleotide cycle (PNC) and reducing tricarboxylic acid (TCA) cycle anaplerosis. The role of the PNC in TCA cycle anaplerosis is still a debated issue in physiology. Using patients with the AMPD1 mutation will allow a human ‘knockout’ approach to answering this question. 2. Muscle AMPD activity and genotype (whole blood AMPD1 analysis) was used to classify participants into three groups: n = 3 with absence of AMPD activity and -/- AMPD1 genotype (homozygous); n = 4 with less than 50 % normal AMPD activity and +/- genotype (heterozygous) and n = 12 with normal AMPD activity and +/+ genotype (control). Biopsies were taken from the vastus lateralis muscle before and after incremental cycle ergometry exercise to exhaustion. The muscle biopsies were analysed for AMPD activity, purine nucleotides/nucleosides and bases, creatine, phosphocreatine, amino acids, and the TCA cycle intermediates malate, citrate and fumarate. 3. Time to exhaustion on the cycle ergometer was not different between groups. Muscle adenosine monophosphate increased significantly with exercise for homozygous subjects as compared with the other groups (P < 0.05). Inosine monophosphate increased significantly after exercise for control (P < 0.05) but not for the homozygous subjects. There were no other between-group differences for any other measured variables. 4. In summary, complete and partial muscle AMPD deficiency did not affect TCA cycle anaplerosis, phosphocreatine hydrolysis, energy charge or exercise performance.